Changes in Sensorimotor Connectivity to dI3 Interneurons in Relation to the Postnatal Maturation of Grasping - Laliberte, Alex M.; Farah, Carl; Steiner, Kyra R.; Tariq, Omar; Bui, Tuan V. (Frontiers in Neural Circuits, 2022)
Primitive reflexes are evident shortly after birth. Many of these reflexes disappear during postnatal development as part of the maturation of motor control. This study investigates the changes of connectivity related to sensory integration by spinal dI3 interneurons during the time in which the palmar grasp reflex gradually disappears in postnatal mice pups. Our results reveal an increase in GAD65/67-labelled terminals to perisomatic Vglut1-labelled sensory inputs contacting cervical and lumbar dI3 interneurons between postnatal day 3 and day 25. In contrast, there were no changes in the number of perisomatic Vglut1-labelled sensory inputs to lumbar and cervical dI3 interneurons other than a decrease between postnatal day 15 and day 25. Changes in postsynaptic GAD65/67-labelled inputs to dI3 interneurons were inconsistent with a role in the sustained loss of the grasp reflex. These results suggest a possible link between the maturation of hand grasp during postnatal development and increased presynaptic inhibition of sensory inputs to dI3 interneurons.